2019
DOI: 10.1108/jima-06-2018-0101
|View full text |Cite
|
Sign up to set email alerts
|

Religion, peculiar beliefs and luxury cars’ consumer behavior in Iran

Abstract: Purpose Religious and peculiar beliefs are two of the factors affecting consumer behavior and may differentially affect individuals and societies. Therefore, this study aims to investigate them from the study of Iranian customers’ behavior. Design/methodology/approach These beliefs are sensitive issues, hence, to investigate them, the grounded theory method through 15 in-depth interviews was applied. Findings The results indicated that evil-eye effect, as a peculiar belief, affected the behavior of luxury … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 48 publications
2
25
0
1
Order By: Relevance
“…This contradicts with other studies where researchers found religion acts as a self-regulating and self-controlling mechanism in individuals (e.g., McCullough & Willoughby, 2009). Such contradictory behavior can be argued to be due to individuals legitimizing their actions, for example, by interpreting religious notions differently (see Forghani et al, 2019).…”
Section: Factors Affecting Ethical Behaviormentioning
confidence: 72%
See 1 more Smart Citation
“…This contradicts with other studies where researchers found religion acts as a self-regulating and self-controlling mechanism in individuals (e.g., McCullough & Willoughby, 2009). Such contradictory behavior can be argued to be due to individuals legitimizing their actions, for example, by interpreting religious notions differently (see Forghani et al, 2019).…”
Section: Factors Affecting Ethical Behaviormentioning
confidence: 72%
“…For example, between religious message and environmental message in advertising to promote green purchasing behavior, the effect was found to be greater using Islamic values as part of the religious message (Siyavooshi, Foroozanfar, & Sharifi, 2019). However, in some cases where the behavior may run contrary to what the religion says, such as spending on luxury items, religion was not a significant predictor (Forghani, Kazemi, & Ranjbarian, 2019). This contradicts with other studies where researchers found religion acts as a self-regulating and self-controlling mechanism in individuals (e.g., McCullough & Willoughby, 2009).…”
Section: Factors Affecting Ethical Behaviormentioning
confidence: 91%
“…For instance, Vitell et al [38] claimed that religiosity affects consumers' behaviors in situations that involve ethical issues. Likewise, Forghani et al [39] reported that religiosity is documented as an important aspect that deeply impacts consumer buying decisions. Similarly, Rakrachakarn et al [40] reported the noteworthy inference that religiosity affects many aspects of the customers' lifestyles that eventually reshape the behavior of selection.…”
Section: Religiosity and Food Waste Intentionmentioning
confidence: 99%
“…Religion is documented as an essential factor that profoundly influences consumer buying decisions [1]. Religion may serve to link consumers to a style of life that determines the pattern of consumption.…”
Section: Introductionmentioning
confidence: 99%